2020
DOI: 10.4269/ajtmh.20-0765
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Response in Latin America

Abstract: Effective management of a pandemic due to a respiratory virus requires public health capacity for a coordinated response for mandatory restrictions, large-scale testing to identify infected individuals, capacity to isolate infected cases and track and test contacts, and health services for those infected who require hospitalization. Because of contextual and socioeconomic factors, it has been hard for Latin America to confront this epidemic. In this article, we discuss the context and the initial responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
170
0
35

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 12 publications
(14 reference statements)
2
170
0
35
Order By: Relevance
“…In addition to its effects of mobility reduction, our analysis also suggests that more swiftly adopted and strictly designed and implemented government policies seem to be associated with lower mortality rates and potentially slower growing mortality rates as other studies have shown [ 2 , 3 , 5 , 9 , 11 , 21 23 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In addition to its effects of mobility reduction, our analysis also suggests that more swiftly adopted and strictly designed and implemented government policies seem to be associated with lower mortality rates and potentially slower growing mortality rates as other studies have shown [ 2 , 3 , 5 , 9 , 11 , 21 23 ].…”
Section: Discussionsupporting
confidence: 66%
“…Several factors may have influenced this differential effectiveness of the closure and restriction policies in reducing mobility in each Latin American country. One factor seems to depend on the degree of compliance of their respective populations [ 8 , 9 , 11 , 12 ]. People living in Argentina, Chile, and Peru were more compliant with these policies than those in Colombia, Brazil, and Mexico, as the higher mobility reductions showed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the appearance of the first cases of COVID-19, Latin American governments have adopted different measures to prevent the advance of the pandemic and mitigate its consequences. The main strategies were the declaration of a national state of health emergency, the closure of international borders, mandatory quarantine of people coming from abroad, promotion of personal hygiene measures, identification and contact of suspected cases, social distancing, voluntary or mandatory confinement, mandatory use of masks; curfews; closure of schools, universities, public spaces, restaurants, bars, and shopping centers, among other measures (Acosta, 2020;Garcia et al, 2020). Likewise, to cushion the negative consequences on the economy, countries have implemented fiscal stimulus plans, despite the economic limitations that many of them face (L opez-Feldman et al, 2020).…”
mentioning
confidence: 99%